Agility moderates the effectiveness of small-sided games versus drill training on fundamental football skills in youth players - Sulisa Sri Purnama; Roma Irawan; Arsil Arsil; Ridho Bahtra (Lentera Negeri, 2026)
Small-sided games (SSG) and analytic drills are widely used to develop fundamental football skills, yet their effectiveness may depend on player characteristics. This study examined the influence of agility on the effectiveness of SSG and drill training for passing, control, and dribbling skills in youth football players. A quasi-experimental 2 × 2 factorial design was employed involving 28 male players aged 10–13 years from SSB Imam Bonjol Padang. Participants were classified into high- and low-agility groups based on Illinois Agility Test scores and assigned to either an SSG or drill training program. Training was conducted over 16 sessions during a 12-week period. Passing-control and dribbling skills were assessed using validated field-based tests. Data were analyzed using two-way ANOVA followed by Tukey HSD post-hoc tests (α = .05). Results showed significant main effects of training method on passing-control (F(1,24) = 6.10, p = .021, η²p = .20) and dribbling (F(1,24) = 9.09, p = .006, η²p = .28). Significant interactions between training method and agility were also found for passing-control (F = 10.13, p = .004, η²p = .30) and dribbling (F = 14.03, p < .001, η²p = .37). Drill training was more effective for high-agility players, whereas SSG produced better outcomes for low-agility players. These findings suggest that agility moderates training effectiveness, highlighting the importance of individualized practice design in youth football development.